Energy loss of light ions (H+ and He+) in matter: high accuracy measurements and comparison with the FEG model - Moro, Marcos Vinicius (2017)
The phenomenon of energy loss that occurs when an ion interacts with matter, also called stopping power, has been investigated for more than a century, and has provided findings of interest. However, reliable procedures for obtaining accurate experimental measurements and a fully theoretical comprehension of the process are tasks still in high demand by the scientific community. Moreover, stopping power data are prerequisites in several applications in modern science, such as engineering, ion implantation and modification of materials, damage to electronics devices (e.g. space radiation), medical physics (e.g. proton therapy), among others. In this thesis we i) develop a rigorous experimental protocol to measure stopping power with high precision, and ii) investigate the collapse of the free electron gas (FEG) model in energy loss of light ions (protons) at a low energy range in transition and rare-earth metals. In the first part, we present an approach to obtain, with high accuracy, the stopping cross sections in the pure materials Al and Mo for protons in the energy range of [0.9 - 3.6] MeV by means of the transmission method. The traceability of the sources of uncertainties are fully evaluated and the final accuracy of the results is 0.63% (0.32% rand. and 0.54% syst.) for Al, and 1.5 % (0.44 % rand. and 1.4% syst.) for Mo, with both results primarily limited by the quality and homogeneity of the stopping foils. For Al, this high accuracy represents an improvement compared to the results obtained in previous studies and serves as a benchmark for our procedure. The most important sources of uncertainties were random - the uncertainty in the peak positions and in the Gaussian fits; and systematic - the non-uniformity thickness of the foils (a special procedure was developed to correct this). Even though the final uncertainty for Mo is higher than for Al, our results improve on the amount of data currently available for the energy range considered. Both data sets are compared with the most commonly employed theoretical models and Monte Carlo codes in the literature. In the second part, electronic stopping cross sections of nontrivial solids, that is, transition and rare earth metals (Ta and Gd) for slow protons are experimentally investigated, and the data were compared with the results for Pt and Au, to understand how energy losses in these metals are correlated with electronic band structures, and to understand the failure of the FEG model predictions. The higher stopping powers found for Ta and Gd cannot be explained by means of the FEG model; however, these effects are successfully correlated with the high density of states (DOS) of both the occupied and unoccupied electronic levels in these metals. For the case of Gd, the experimental data are extended in the energy range until the Bragg\'s peak is reached. The two parts of this thesis were published in Physical Review A 93 022704 (2016), and in Physical Review Letters 18 103401 (2017), respectively.